Inhibition of platelet aggregation by a monoclonal antibody against human fibronectin. - Dixit, V M (1985)
A monoclonal antibody (A3.3) has been generated against human platelet fibronectin (FN). A3.3 reacts with human plasma FN but with no other plasma proteins. A3.3 was found to inhibit thrombin- or ionophore A23187-stimulated aggregation of gel-filtered platelets in a concentration-dependent manner in both an aggregometer assay and a sensitive well plate aggregation assay. The antibody does not block secretion of serotonin. Four other anti-FN monoclonal antibodies that recognize different epitopes on FN than A3.3 does have no effect on platelet aggregation. A3.3 does not block the adhesion of CHO cells to FN-coated surfaces, indicating that it does not bind to the identified cell-binding domain of FN. A3.3 reacts with a 160/140-kDa doublet, known to contain the cell-binding domain, that is produced by digestion of FN with elastase or thermolysin. However, the antibody does not react with lower molecular weight species that also contain the cell-binding domain or with any of the other identified domains of FN. The A3.3 epitope is extremely protease sensitive and the smallest fragment found in any digest that retains reactivity with A3.3 is a 70-kDa peptide produced in low yield by mild thermolytic cleavage of FN. These data suggest that A3.3 defines a functional site present on both the platelet and plasma FN molecule that has a direct role in platelet aggregation.